Observation of multiple sausage oscillations in cool post-flare loop - A. K. Srivastava; T. V. Zaqarashvili; W. Uddin; B. N. Dwivedi (My University, 2008)
Using simultaneous high spatial (1.3 arcsec) and temporal (5 and 10 s) resolution Hα observations from the 15 cm Solar Tower Telescope at Aryabhatta Research Institute of Observational Sciences (ARIES), we study the oscillations in the relative intensity to explore the possibility of sausage oscillations in the chromospheric cool post-flare loop. We use the standard wavelet tool, and find the oscillation period of ≈587 s near the loop apex, and ≈349 s near the footpoint. We suggest that the oscillations represent the fundamental and the first harmonics of the fast-sausage waves in the cool post-flare loop. Based on the period ratio P1/P2∼1.68, we estimate the density scaleheight in the loop as ∼17 Mm. This value is much higher than the equilibrium scaleheight corresponding to Hα temperature, which probably indicates that the cool post-flare loop is not in hydrostatic equilibrium. Seismologically estimated Alfven speed ´ outside the loop is ∼300–330 km s−1. The observation of multiple oscillations may play a crucial role in understanding the dynamics of lower solar atmosphere, complementing such oscillations already reported in the upper solar atmosphere (e.g. hot flaring loops).
Keywords: MHD – waves – Sun: chromosphere – Sun: flares – Sun: oscillations.